Determination Of Flood Inundation For Sungai Bertam By Hydraulic Physical Model - Rohalim, Nurfatihah Idayu (Universiti Sains Malaysia, 2018)
Dams are constructed as water storage to compensate for fluctuations in catchment area and to generate electricity. However, uncontrollable amount of discharges released from the gated spillways of the dam would impact the downstream area. On October 23 2013, floods occurred in downstream of Sungai Bertam probably due to a huge volume of discharges were released from Sultan Abu Bakar (SAB) dam. Impacts of that flood, three people were confirmed dead and nearly 100 houses destroyed or under water while over 100 vehicles badly damaged. Thus, study on various discharges released along the river was conducted. The main objective in this study is to determine the maximum discharge without any flood inundation at Kampung Baru Lembah Bertam for 175 m3/s for 100 year ARI. The flood water level can help evaluate effect of in that area due to SAB dam release. The physical model testing was done to analyse various discharges released. After the physical model testing, Surfer software was used to illustrate the condition and risk area of flooding. The amount of discharges release used in the experiment was 8, 16, 24, 32, 40, 48 and 56 l/s. The water discharges were based on recommendation dam release by Tenaga Nasional Berhad (TNB). As a result, maximum depth, maximum velocity, and inundation illustration were produced. This finding will be able to predict risk area of flooding. This study will also help authorities to control amount of maximum discharge level allowed from the dam as to prevent flood occur in downstream area of Sungai Bertam.